Research progress of bone metastases: From disease recognition to clinical practice - Yang, Wenbo; Pan, Qing; Huang, Fuhua; Hu, Hongzhi; Shao, Zengwu (Frontiers in Oncology, 2023)
Bone metastases, as one of the common types of metastatic tumors, have a great impact on the survival period and quality of life of patients. Bone metastases are usually characterized by bone destruction, which tends to occur in the spine, pelvis, and femur. Skeletal related events caused by bone destruction often lead to pain, pathological fractures and even paralysis. Given the serious clinical consequences of bone metastases, a thorough understanding of the disease is necessary for clinicians. In this review, we provide a detailed explanation of bone metastases from the epidemiology, clinical features, pathogenesis, and recently developed clinical treatment protocols. We concluded that the incidence of bone metastases is increasing gradually, with serious clinical symptoms, complex pathogenesis and diverse clinical treatment. According to existing research, the core purpose of the treatment of bone metastases is to alleviate symptoms and reduce or delay the occurrence of pain or bone-related events. We believe that the future treatment of bone metastases will be diversified and comprehensive. Some advanced technologies, such as nanomedicine, could be used for treatment, but this depends on understanding how disease occurs. With the development of treatment, the survival time and quality of life of patients will be improved.